Facilitative and competitive effects of bracken fronds and litter on tree seedling recruitment - López, Cecilia L.; Mayta, Cesar; Soliz, Andrea; Hensen, Isabell; Gallegos, Silvia C. (Frontiers in Ecology and Evolution, 2025)
IntroductionTropical montane forests are diverse ecosystems increasingly threatened by land-use change and frequent uncontrolled fires caused by humans. After these fires, affected areas are often dominated by ferns of the genus Pteridium (bracken), delaying the rate of forest regeneration. This study examined the facilitative and competitive roles of bracken fronds and litter on seedling establishment, recruitment success, and growth after 36 months, and the extent to which these effects depend on seed size in early plant development processes.MethodsAt eight sites, we conducted seed addition and seedling-transplant experiments in plots established in bracken-dominated areas, using the following treatments: (a) fronds and litter intact (F+L+); (b) fronds intact and litter removed (F+L−); (c) fronds removed and litter intact (F−L+); and (d) fronds and litter removed (F−L−).ResultsA total of 46,640 seeds from 24 tree species were sown and 1,070 nursery-raised seedlings transplanted. In treatments with fronds and litter, seedling establishment and recruitment success increased with seed size. In contrast, in the treatment without fronds and litter all the species had low performance. Fronds proved to be highly beneficial for all seed sizes and for all early development processes. Litter, on the other hand, had negative effects on small-seeded species during establishment, but had neutral to positive effects on the recruitment and growth of all species.DiscussionThe disadvantage of small seeds under bracken litter may be related to the high light requirements of seedlings, as litter accumulation reduces light transmission. Species with large seeds and shade tolerance benefit from bracken frond cover, suggesting that restoration strategies in bracken-dominated areas should prioritize these species. Moreover, planting seeds or seedlings shortly after fire, in the presence of bracken fronds and before litter accumulation would be most beneficial for tree species. Additionally, seed dispersers play a crucial role in transporting large seeds into bracken-dominated areas, emphasizing the need for an integrated approach that considers biotic and abiotic factors for effective forest recovery.